Critical Discourse Analysis Lens: Gender Power Relations in The Movie KKN di Desa Penari - Hasanah, Ummi; Pritia, Dian Aulia; Septiani, Ghana Aldila; Hidayat, Rifki Maulana (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
Gender power relations have also experienced significant shifts in meaning. In contrast to the past, where gender power relations were dominated by men as the holders of power, today, women also play similar roles. Modern women have become more courageous in expressing themselves and interacting freely. This study aims to explore the representation of power relations based on gender differences found in the film KKN di Desa Penari directed by Awi Suryadi. The article discusses in detail the roles and social norms that influence gender relations in each character of the movie  KKN di Desa Penari . To achieve the research objectives, this study applies Norman Fairclough's Critical Discourse Analysis (CDA), which allows for an in-depth understanding of the power relations experienced by each character in the film. Fairclough's CDA encompasses three levels of analysis: micro (text), meso (text production and consumption), and macro (social context). The results of the analysis reveal that gender-based power relations in this film are depicted through power dynamics in several types of relationships: (1) power relations in friendship, where power dynamics in friendships are influenced by gender; (2) power relations in romantic relationships, where the power dynamics between two individuals are influenced by their love for each other; (3) power relations in familial relationships, where power dynamics arise due to kinship ties; and (4) power relations in workplace relationships, which are also commonly found as the workplace is a place where power dynamics are visibly represented. The findings of this study highlight the complexity and significance of gender-based power dynamics in shaping social relationships, particularly in the Javanese cultural context portrayed in the film.